Improving Science Learning Outcomes on Seasons and Climate Through Discussion Methods Using Student Worksheets Among Fourth-Grade Students at SDN Banyuajuh 5 - Ilham Handika; Nadhira Amalia; Mir'ah Zahra Rifdani; Badruddin; Yuyung Sugianto (Yayasan Citra Dharma Cindekia, 2026)
Improving Science Learning Outcomes on the Topic of Seasons and Climate through the Discussion Method with Student Worksheets (LKPD) for Grade IV Students at SDN Banyuajuh 5. This study aims to improve students' Science learning outcomes on the topic of seasons and climate through the implementation of the discussion method with the assistance of Student Worksheets (LKPD). This research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of this study were 9 fourth-grade students of SDN Banyuajuh 5. The data collected included quantitative and qualitative data. Quantitative data were obtained through students' learning achievement tests, while qualitative data were collected through observations of students' activities during the learning process. The results of the study showed an improvement in students' learning outcomes in each cycle. In Cycle I, the percentage of students achieving learning mastery was 11%, while in Cycle II it increased to 100%. This improvement was accompanied by an increase in students' learning activities, which changed from the less active category in Cycle I to the highly active category in Cycle II. These findings indicate that the implementation of the discussion method with LKPD was effective in improving students' learning outcomes. In addition, students became more active in discussions, demonstrated better cooperation in group activities, and showed greater confidence in expressing their opinions during the learning process. Therefore, it can be concluded that the implementation of the discussion method with LKPD can improve Science learning outcomes on the topic of seasons and climate for Grade IV students at SDN Banyuajuh 5.